151 Nuclear magnetic resonance profiling of serum identifies novel biomarker associated with coronary atherosclerosis. (16th May 2012) - Tan, S T; Sehmi, J; Al-Hussaini, A; Ala-Korpela, M; Elliott, Paul; Chambers, J C; Kooner, J S
Abstract : Introduction: Coronary heart disease (CHD) is the leading cause of death worldwide. Current CHD risk prediction tools do not accurately identify risk of CHD in all populations. There is an urgent need for discovery of novel biomarkers to help understand mechanisms underlying CHD and improve risk functions to identify people at increased risk. We used serum metabonomic nuclear magnetic resonance (NMR) profiling to identify biomarkers associated with the presence of coronary artery calcification (CAC), a quantitative measure of coronary atherosclerosis. Methods: We investigated 2358 men and women aged 35–75 years participating in the London Life Sciences Population (LOLIPOP) Study. Participants with prior history of CHD were excluded. All participants completed a structured health questionnaire, underwent physical assessment and had blood collected after an 8 h fast. CAC was quantified using electron beam CT. Quantitative NMR spectroscopy was used to characterise serum samples for lipoproteins, fatty acids and low molecular weight markers. Linear regression was used to determine the relationship between metabolites and Agatston score. Statistical significance was inferred at p<0.0013, corresponding to a Bonferroni correction for 39 primary NMR measures. Results: CAC was associated with older age, male gender, cigarette smoking, raised systolic and diastolic blood pressure, obesity and hypercholesterolaemia. Among the 39 NMR measures, 11 were associated with CAC after adjustment for age, sex and ethnicity (p=0.0013 to p=5.0×10 −12 ). In multivariate analysis, after further adjustment for conventional risk factors, we identified an association of the metabonomic biomarker (an abundant naturally occurring non-essential amino acid) with coronary artery calcium (p=7.9×10 −4 ). The OR for the presence of significant coronary atherosclerosis (CAC>100) was 2.21 (95% CI 1.59 to 3.07, p=2.2×10 −6 ) among people in the lowest quartile for the novel metabolite, compared to those in the highest quartile, implying that lower levels of the metabonomic biomarker confers increased CHD risk. Conclusions: Using NMR spectroscopy, we have identified a novel metabonomic biomarker to be independently associated with CAC, a measure of coronary atherosclerosis. Further testing in large prospective cohorts is required to evaluate the predictive value of this novel metabonomic biomarker to CHD.